Analisis Kesuksesan Penerapan Sistem Informasi pada Sistem Informasi Pelayanan Terpadu (SIPT) Online - Susanti Purwaningsih (STIE Widya Manggala, 2010)
Sistem Informasi Pelayanan Terpadu (SIPT) Online PT Jamsostek (Persero) is an implemented Information System by PT Jamsostek (Persero) to support service for member of social security program in Indonesia. This research is to test whether system quality, information quality, and service quality positively affect on user satisfaction and to test whether system quality, information quality, service quality positively, task-technology fit, and user satisfaction have positive effect on indvidual impact.. Model used in this research was DeLone and McLean’s Information System Success Model (1992), which was modified by adding construct of service quality, task-technology fit and eliminating construct of use and organizational impact of the model. The research was done on employee in PT Jamsostek (Persero) branch offices in Indonesia. Data was obtained by mail survey. 519 questionnaires collected and analysed by using software Smart PLS version 2.0.. The result of test indicated that user satisfaction is significantly influenced by system quality, information quality, and service quality. In addition individual impact due to system use is significantly influenced by system quality, information quality, service quality, task-technology fit, and user satisfaction.